Resistance to antibacterial antifolates in multidrug-resistant Staphylococcus aureus: prevalence estimates and genetic basis. (20th March 2023) - Kime, Louise; Waring, Tina; Mohamad, Merianne; Mann, Benjamin F; O'Neill, Alex J
Abstract: Objectives: Antibacterial antifolate drugs might have a wider role in the management of staphylococcal infection. One factor that could potentially limit their use in this context is pre-existing resistance. Here we explored the prevalence and genetic basis for resistance to these drugs in a large collection ( n = 1470) of multidrug-resistant (MDR) Staphylococcus aureus . Methods: Strains were subjected to susceptibility testing to detect resistance to trimethoprim, sulfamethoxazole, co-trimoxazole and the investigational drug, iclaprim. Whole-genome sequences were interrogated to establish the genetic basis for resistance. Results: According to CLSI breakpoints, 15.2% of the strains were resistant to trimethoprim, 5.2% to sulfamethoxazole and 4.1% to co-trimoxazole. Using the proposed breakpoint for iclaprim, 89% of the trimethoprim-resistant strains exhibited non-susceptibility to this agent. Sulfamethozaxole resistance was exclusively the result of mutation in the drug target (dihydropteroate synthase). Resistance to trimethoprim and iclaprim also resulted from mutation in the target (dihydrofolate reductase; DHFR) but was more commonly associated with horizontal acquisition of genes encoding drug-insensitive DHFR proteins. Among the latter, we identified a novel gene ( dfrL ) encoding a DHFR with ∼35% identity to native and known resistant DHFRs, which was confirmed via molecular cloning to mediate high-level resistance. Conclusions: This study provides a detailed picture of the genotypes underlying staphylococcal resistance to antifolate drugs in clinical use and in development. Prevalence estimates suggest that resistance to the diaminopyrimidines (trimethoprim/iclaprim) is not uncommon among MDR S. aureus, and considerably higher than observed for sulfamethoxazole or co-trimoxazole.